Communicating uncertainty in risk descriptions: the consequences of presenting imprecise probabilities in time critical decision-making situations. Issue 5 (4th May 2021) - Rydmark, Joacim; Kuylenstierna, Jan; Tehler, Henrik
Abstract: One important question concerning a risk description is to what extent it should contain information about the uncertainty surrounding an estimated probability for an event, for example, by using some form of probability range. Presenting a point estimate together with a range can inform the decision-maker about both the best judgement as well as the strength of knowledge regarding the probability in question, so that the decision-maker can take this information into consideration when making decisions. However, communicating uncertainty in risk descriptions may lead to delays in the decision-making process, due to people's general aversion to ambiguity and other forms of uncertainty. This can be devastating in time critical decision-making situations, where delaying decisions leads to substantial costs or losses - as in the case of a military command and control (C2) situation or in crisis response management (CRM). This study investigated how 106 university students handled a fictive time critical military decision-making situation with imprecise probabilities presented in the form of ranges. The purpose was to make a first estimation regarding if presenting uncertainty in risk descriptions could be a problem in these kinds of situations. The results show that almost half of the participants delayed their decisions and that many participants showed little restraint regarding their waiting time. These results indicate that communicating uncertainty in risk descriptions can be a problem in time critical decision-making situations, and that presenting uncertainty in risk descriptions may require decision-makers to be educated in the specific problems associated with decision-making in these types of situations.